2021
DOI: 10.7759/cureus.13493
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of Right-Sided Symptom Onset as a Predictor of Poor Parkinson’s Disease Prognosis

Abstract: Objective The current study aimed to measure and compare neurological disability in Parkinson’s disease (PD) patients with right-sided symptom onset with that in PD patients with left-sided symptom onset, using the measurements taken at their first and last visits, to determine if right-sided symptom onset was predictive of a poor PD prognosis. Methods One hundred and forty-three PD patients were included in the study. The Unified Parkinson’s Disease Rating Scale (UPDRS) and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Clinically, this could indicate a worse clinical prognosis for D-PD, consistent with previously published literature. 11,12,25 Heinrichs-Graham et al used magnetoencephalography to evaluate the relationship between symptom asymmetry and the laterality of neural activity, also concluding that the ND-PD group presented healthier oscillatory neural activity patterns than the D-PD group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinically, this could indicate a worse clinical prognosis for D-PD, consistent with previously published literature. 11,12,25 Heinrichs-Graham et al used magnetoencephalography to evaluate the relationship between symptom asymmetry and the laterality of neural activity, also concluding that the ND-PD group presented healthier oscillatory neural activity patterns than the D-PD group.…”
Section: Discussionmentioning
confidence: 99%
“…Scharoun et al 4 found right‐handed D‐PD increased non‐dominant hand usage, potentially switching hand preference as the disease progresses. Some research suggests D‐PD has a more debilitating effect on hand performance than ND‐PD, 10 while other studies report faster motor progression for ND‐PD 4,5 or D‐PD 11,12 . Quantifying asymmetrical motor impairment could help clinicians confirm PD diagnosis, refine prognosis, and design personalized rehabilitation plans.…”
mentioning
confidence: 99%
“…Our patient had right-lateralized hemichorea-hemiballismus as a result of a lesion occurring in the left caudate nucleus head caused by hypoglycemia. It is also claimed that the left hemisphere was more vulnerable to the pathophysiological processes than the right hemisphere and the prognosis of Parkinson’s patients with clinical symptoms from the left hemisphere is significantly worse [ 9 ].…”
mentioning
confidence: 99%